2022
DOI: 10.3389/fgwh.2022.887541
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Depot Medroxyprogesterone Acetate Intramuscular Injection, Copper Intrauterine Device and Levonorgestrel Implant Contraception on Estradiol Levels: An Ancillary Study of the ECHO Randomized Trial

Abstract: IntroductionHormonal contraception affects endogenous sex steroid levels. Robust evidence from randomized trials of the relative effects of different contraceptive methods is scarce. We compared the effects of three contraceptive methods on serum estradiol levels using data from women (18–35 years) requesting contraception in the Evidence for Contraceptive Options and HIV Outcomes (ECHO) randomized trial.MethodsWomen were randomly allocated to the depot medroxyprogesterone acetate intramuscular (DMPA-IM) injec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 18 publications
(20 reference statements)
1
2
0
Order By: Relevance
“…The effects were not significantly different between groups. Our findings of estradiol serum concentrations for DMPA-IM of 76.5 pmol/L (IQR 54.1 to 104.2) are similar to values reported in the literature, which range from 37-367 pmol/L [32,36,[49][50][51][52][53][54]. However, our findings of estradiol serum concentrations for NET-EN of 69.8 pmol/L (55.1 to 89.3), are lower than some but not all of those usually reported, which range from 135-2820 pmol/L [35,[55][56][57].…”
Section: Plos Onesupporting
confidence: 90%
See 1 more Smart Citation
“…The effects were not significantly different between groups. Our findings of estradiol serum concentrations for DMPA-IM of 76.5 pmol/L (IQR 54.1 to 104.2) are similar to values reported in the literature, which range from 37-367 pmol/L [32,36,[49][50][51][52][53][54]. However, our findings of estradiol serum concentrations for NET-EN of 69.8 pmol/L (55.1 to 89.3), are lower than some but not all of those usually reported, which range from 135-2820 pmol/L [35,[55][56][57].…”
Section: Plos Onesupporting
confidence: 90%
“…The latter likely include effects on vaginal microbiome composition, genital tract integrity, immune function and susceptibility to and transmission of HIV and other infections [ 12 , 13 ]. DMPA-IM use is associated with lower estrogen levels compared with no HC, as well as users of other HCs such as the LNG intrauterine system, and the etonogestrel and LNG implants [ 12 , 13 , 32 ]. Some reports suggest that DMPA-IM results in hypoestrogenic effects with estradiol levels similar to postmenopausal levels [ 13 , 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…This is biologically plausible because of the known effects of DMPA-IM on suppression of endogenous estrogen and testosterone, both of which are considered to enhance libido. Ancillary hormonal studies of the ECHO Trial at the East London, South Africa site found lower estradiol levels at 6 months in women randomized to DMPA-IM than those randomized to the Cu-IUD and the LNG implant, and the implant group were significantly lower than with the Cu-IUD [18]. Free testosterone was significantly lower with DMPA-IM than with the LNG implant, with the Cu-IUD being intermediate.…”
Section: Plos Onementioning
confidence: 99%